Stability Constants of the Ternary Complexes of Copper(II) with Dipicolinic Acid and Amino Acids - Kulkarni, V.D.; Pujar, M.A.; Suresh, T. (Asian Journal of Chemistry, 2010)
The stability constants of mixed-ligand complexes of the type (CuXY) where X = 2,6-pyridinedicarboxylic acid (dipicolinic acid) as the primary ligand and Y = DL-α-alanine, β-alanine, glycine or glutamic acid as secondary ligand have been determined in aqueous solution using pH-metric technique. The stability constants have been evaluated at 25ºC and at 0.1 M ionic strength. Copper (II) formed 1 : 1 : 1 mixed-ligand complexes with dipicolinic acid and amino acids. The preferential formation of the ternary complexes over the binary complexes have been discussed in terms of equilibrium constants.